Seedling traits, plasticity and local differentiation as strategies of invasive species of Impatiens in central Europe - Skálová, Hana; Havlícková, Vendula; Pysek, Petr (Annals of botany, 2012)
BACKGROUND AND AIMS: Invasiveness of some alien plants is associated with their traits, plastic responses to environmental conditions and interpopulation differentiation. To obtain insights into the role of these processes in contributing to variation in performance, we compared congeneric species of Impatiens (Balsaminaceae) with different origin and invasion status that occur in central Europe. METHODS: Native I. noli-tangere and three alien species (highly invasive I. glandulifera, less invasive I. parviflora and potentially invasive I. capensis) were studied and their responses to simulated canopy shading and different nutrient and moisture levels were determined in terms of survival and seedling traits. KEY RESULTS AND CONCLUSIONS: Impatiens glandulifera produced high biomass in all the treatments and the control, exhibiting the 'Jack-and-master' strategy that makes it a strong competitor from germination onwards. The results suggest that plasticity and differentiation occurred in all the species tested and that along the continuum from plasticity to differentiation, the species at the plasticity end is the better invader. The most invasive species I. glandulifera appears to be highly plastic, whereas the other two less invasive species, I. parviflora and I. capensis, exhibited lower plasticity but rather strong population differentiation. The invasive Impatiens species were taller and exhibited higher plasticity and differentiation than native I. noli-tangere. This suggests that even within one genus, the relative importance of the phenomena contributing to invasiveness appears to be species' specific.
Keywords: Plant Shoots; biomasa; druhová specificita; semenáček; fenotyp; životní prostředí; Phenotype; Biomass; Environment; Impatiens; výhonky rostlin; Adaptation, Physiological; Droughts; Plant Roots; Europe; stonky rostlin; fyziologická adaptace; Species Specificity; Plant Stems; kořeny rostlin; Evropa; zavlečené druhy; Seedlings; záplavy; Introduced Species; Floods; období sucha